Measurement of muon plus proton final states in nu(mu) interactions on hydrocarbon at < E-nu >=4.2 GeV - Walton, T (2015)
A study of charged-current muon neutrino scattering on hydrocarbon (CH) in which the final state includes a muon, at least one proton, and no pions is presented. Although this signature has the topology of neutrino quasielastic scattering from neutrons, the event sample contains contributions from quasielastic and inelastic processes where pions are absorbed in the nucleus. The analysis accepts events with muon production angles up to 70◦ and proton kinetic energies greater than 110 MeV. The cross section, when based completely on hadronic kinematics, is well-described by a relativistic Fermi gas nuclear model including the neutrino event generator modeling for inelastic processes and particle transportation through the nucleus. This is in contrast to the quasielastic cross section based on muon kinematics, which is best described by an extended model that incorporates multi-nucleon correlations. This measurement guides the formulation of a complete description of neutrino-nucleus interactions that encompasses the hadronic as well as the leptonic aspects of this process.